Teachers' Perceptions of Academic Supervision in a Pandemic Era; Phenomenological Review - Nuryani, Lilis Kholisoh; Enas, Enas; Herman, Maman; Wahyudi, Eko; Dianawati, Lely (JURNAL AL-TANZIM, 2022)
Academic supervision is non-negotiable for leaders to improve teacher professionalism in schools. This research aims to understand the teacher's perception of the principal's academic supervision at SMP Negeri 2 Kroya. This study uses a qualitative approach to the type of phenomenology. This research is an understanding of social phenomena or phenomena that occur in the field, with more emphasis on a complete picture of the phenomena that occur. The results showed that teachers' perceptions of academic supervision by school principals had a perfect meaning because, on average, they had good motivation and performance before the covid-19 pandemic. Teachers interpreted the supervision carried out by the principal of SMP Negeri 2 Kroya as professional guidance assistance, quality-oriented based on continuous improvement, quality control, driving school principals, and an arena for the principal's responsibility to teachers.